LEADERSHIP AND CONTEMPORARY PUBLIC POLICY - Nurdiyansah, Andri; Rohayati, Yeti; Achmad Syam, Rifqi Zaeni (LPPM Politeknik Pajajaran ICB, 2024)
Government leadership in a government area is largely determined by the capabilities of each leader. The capability referred to is the ability to carry out government tasks in accordance with the needs and interests of its people as well as the demands of the global community. It takes a leader's ability to understand the aspirations of his people and read the trends of the changing times. Contemporary public policies need to be studied carefully so that strategic issues can be selected from among the issues faced to be raised as policy problems and subsequently can be determined as a policy agenda (agenda setting). A careful study through these stages will greatly assist the government in formulating policies in the form of legislation that can be used as leverage in solving various problems faced by the government. Starting from the determination of policy issues to the right policy formulation, various programs and activities that are right on target can be operationalized. Through this stage, an accountable government administration will also be able to achieve a significant impact on improving the welfare of the community.